Clinical variables, not RAAS polymorphisms, predict blood pressure response to ACE inhibitors in Sardinians. (October 2008) - Filigheddu, Fabiana; Argiolas, Giuseppe; Bulla, Emanuela; Troffa, Chiara; Bulla, Patrizia; Fadda, Simone; Zaninello, Roberta; Degortes, Simona; Frau, Francesca; Pitzoi, Silvia; Glorioso, Nicola
Aim: No definite factors predict blood pressure response to angiotensin-converting enzyme-inhibitors. The aim of this study was to test the association of gene polymorphisms of the renin––angiotensin––aldosterone system with essential hypertension and anthropometric variables, intermediate phenotypes and gene polymorphisms with blood pressure after fosinopril in a genetically homogeneous cohort.Methods: A total of 630 essential hypertension patients, not previously treated or out of antihypertensive treatment for at least 6 months versus 219 normotensives (genotype frequencies, χχ 2 ). A total of 191 patients were randomly assigned to fosinopril 20 mg/day. Samples for plasma renin activity and aldosterone, 24-h urinary sodium (flame photometry) were collected. Gene polymorphisms –– angiotensin-converting enzyme (insertion/deletion), angiotensin II type 1-receptor (A1166C), aldosterone synthase (-344C/T) and angiotensinogen (-6A/G) –– were analyzed by standard techniques. The association of anthropometric variables, intermediate phenotypes and gene polymorphisms with blood pressure after 4 weeks therapy was tested by univariate analysis and analysis of covariance model (Intercooled Stata SE 9.2).Results: No genetic polymorphisms were associated with essential hypertension, blood pressure response and intermediate phenotypes (p > 0.05). Systolic blood pressure after therapy was associated with baseline systolic blood pressure, age and sex.Conclusions: Our results confirm the difficulty in dissecting both essential hypertension and pharmacogenomics when analyzing the effect of single genes in complex multifactorial traits.